PEMIKIRAN PENDIDIKAN ISLAM SYEKH BURHANUDDIN DALAM BUKU KARANGAN RAUF PAKIE MALANO DAN ABDUL MANAF - Ratna Kumala Dewi; Jarudin; Meri Erawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One of the reasons behind the researcher in conducting this study is the publication of a manuscript about Syech Burhanuddin stored in the National Library, the manuscript provides an important contribution in revealing the intellectual history of Islam in Minangkabau. In addition, Syech Burhanuddin is known as a central figure who introduced the first Islamic educational institution in the Minangkabau region, so that his existence has historical and pedagogical significance that deserves further exploration. Based on these considerations, the researcher is interested in raising a study with the title "Islamic Educational Thoughts of Syech Burhanuddin in the Book Written by Rauf Pakie Malano and Abdul Manaf." Through this research, it is hoped that it can contribute to increasing understanding of the history and development of Islamic education in Minangkabau in a more in-depth and contextual manner.